OpenStudy (anonymous):

Given: 2x – 3(x – 5 + x) = 2x – 3 Prove: x = 3 What are the missing justification steps, in order? Distributive Property, Associative Property of Addition, Combine Like Terms Subtraction Property of Equality, Associative Property of Addition, Addition Property of Equality Subtraction Property of Equality, Commutative Property of Addition, Addition Property of Equality Distributive Property, Commutative Property of Addition, Combine Like Terms

6 years ago
OpenStudy (anonymous):

Mathematical Statement Justification 2x – 3(x - 5 + x) = 2x - 3 Given 2x – 3(x + x – 5) = 2x – 3 Commutative Property of Addition 2x – 3(2x – 5) = 2x – 3 Combine Like Terms 2x – 6x + 15 = 2x – 3 (2x – 6x) + 15 = 2x – 3 – 4x + 15 = 2x – 3 – 6x + 15 = – 3 Subtraction Property of Equality – 6x = – 18 Subtraction Property of Equality x = 3 Division Property of Equality

6 years ago
jimthompson5910 (jim_thompson5910):

going from 2x – 3(2x – 5) = 2x – 3 to 2x – 6x + 15 = 2x – 3 what property are we using here?

6 years ago
OpenStudy (anonymous):

Distributive ?

6 years ago
jimthompson5910 (jim_thompson5910):

yes you got it

6 years ago
jimthompson5910 (jim_thompson5910):

so the answer is either Distributive Property, Associative Property of Addition, Combine Like Terms OR Distributive Property, Commutative Property of Addition, Combine Like Terms

6 years ago
jimthompson5910 (jim_thompson5910):

6 years ago
jimthompson5910 (jim_thompson5910):

going from 2x – 6x + 15 = 2x – 3 to (2x – 6x) + 15 = 2x – 3 what is happening (which property are we using now)?

6 years ago
OpenStudy (anonymous):

then associative property and then combine like terms

6 years ago
jimthompson5910 (jim_thompson5910):

you got it

6 years ago
OpenStudy (anonymous):

thank you thank you :)

6 years ago
jimthompson5910 (jim_thompson5910):

you're welcome

6 years ago